![見出し画像](https://assets.st-note.com/production/uploads/images/72056042/rectangle_large_type_2_33f6ff2b626b544c82ec83f32a5b4fd6.png?width=1200)
PRML 第1章 1.11(基本)
$$
\begin{array}{ll}
(1.54) & \ln p(\mathbf{x} | \mu,\sigma^2) = -\dfrac{1}{2\sigma^2} {\displaystyle \sum_{n=1}^N} (x_n - \mu)^2 - \dfrac{N}{2} \ln\sigma^2 - \dfrac{N}{2} \ln(2\pi)\\[1em]
(1.55) & \mu_{\scriptscriptstyle\mathrm{ML}} = \dfrac{1}{N} {\displaystyle \sum_{n=1}^N} x_n\\[1em]
(1.56) & \sigma_{\scriptscriptstyle\mathrm{ML}}^2 = \dfrac{1}{N} {\displaystyle \sum_{n=1}^N} (x_n - \mu_{\scriptscriptstyle\mathrm{ML}})^2
\end{array}
$$
解答
(1.54)を$${\mu}$$で微分すると,
$$
\begin{array}{l}
\dfrac{\partial}{\partial\mu} \ln p(\mathbf{x} | \mu,\sigma^2) = -\dfrac{1}{2\sigma^2} \dfrac{\partial}{\partial\mu} {\displaystyle \sum_{n=1}^N} (x_n - \mu)^2 = \dfrac{1}{\sigma^2} {\displaystyle \sum_{n=1}^N} (x_n - \mu)
\end{array}
$$
となる.これが0であることから,
$$
\begin{array}{l}
{\displaystyle \sum_{n=1}^N} (x_n - \mu_{\scriptscriptstyle\mathrm{ML}}) = 0 \quad\Longleftrightarrow\quad {\displaystyle \sum_{n=1}^N} x_n - N\mu_{\scriptscriptstyle\mathrm{ML}} = 0 \qquad\therefore \mu_{\scriptscriptstyle\mathrm{ML}} = \dfrac{1}{N} {\displaystyle \sum_{n=1}^N} x_n
\end{array}
$$
となり,(1.55)が成り立つ.
また,(1.54)で$${\mu = \mu_{\scriptscriptstyle\mathrm{ML}}}$$として$${\sigma^2}$$で微分すると,
$$
\begin{array}{l}
\dfrac{\partial}{\partial\sigma^2} \ln p(\mathbf{x} | \mu_{\scriptscriptstyle\mathrm{ML}},\sigma^2) = \dfrac{1}{2\sigma^4} {\displaystyle \sum_{n=1}^N} (x_n - \mu_{\scriptscriptstyle\mathrm{ML}})^2 - \dfrac{N}{2\sigma^2}
\end{array}
$$
となる.これが0であることから,
$$
\begin{array}{l}
\dfrac{1}{2\sigma_{\scriptscriptstyle\mathrm{ML}}^4} \left( {\displaystyle \sum_{n=1}^N} (x_n - \mu)^2 - N\sigma_{\scriptscriptstyle\mathrm{ML}}^2 \right) = 0
\qquad\therefore \sigma_{\scriptscriptstyle\mathrm{ML}}^2 = \dfrac{1}{N} {\displaystyle \sum_{n=1}^N} (x_n - \mu_{\scriptscriptstyle\mathrm{ML}})^2
\end{array}
$$
となり,(1.56)が成り立つ.